Integrated stress response in hepatitis C promotes Nrf2-related chaperone-mediated autophagy: A novel mechanism for host-microbe survival and HCC development in liver cirrhosis. (May 2020) - Dash, Srikanta; Aydin, Yucel; Wu, Tong
Abstract: The molecular mechanism(s) how liver damage during the chronic hepatitis C virus (HCV) infection evolve into cirrhosis and hepatocellular carcinoma (HCC) is unclear. HCV infects hepatocyte, the major cell types in the liver. During infection, large amounts of viral proteins and RNA replication intermediates accumulate in the endoplasmic reticulum (ER) of the infected hepatocyte, which creates a substantial amount of stress response. Infected hepatocyte activates a different type of stress adaptive mechanisms such as unfolded protein response (UPR), antioxidant response (AR), and the integrated stress response (ISR) to promote virus-host cell survival. The hepatic stress is also amplified by another layer of innate and inflammatory response associated with cellular sensing of virus infection through the production of interferon (IFN) and inflammatory cytokines. The interplay between various types of cellular stress signal leads to different forms of cell death such as apoptosis, necrosis, and autophagy depending on the intensity of the stress and nature of the adaptive cellular response. How do the adaptive cellular responses decode such death programs that promote host-microbe survival leading to the establishment of chronic liver disease? In this review, we discuss how the adaptive cellular response through the Nrf2 pathway that promotes virus and cell survival. Furthermore, we provide a glimpse of novel stress-induced Nrf2 mediated compensatory autophagy mechanisms in virus-cell survival that degrade tumor suppressor gene and activation of oncogenic signaling during HCV infection. Based on these facts, we hypothesize that the balance between hepatic stress, inflammation and different types of cell death determines liver disease progression outcomes. We propose that a more nuanced understanding of virus-host interactions under excessive cellular stress may provide an answer to the fundamental questions why some individuals with chronic HCV infection remain at risk of developing cirrhosis, cancer and some do not.